Dermoscopy click of tricky tick infestation from an urban area - Awake, Praneet P.; Ketaki Pathak; Sourav Sen (Journal of Pakistan Association of Dermatologists, 2022)
Ticks are ecto-parasites that live in woods or on animals and feed on blood. They act as vectors for transmission of various infectious diseases in human beings. Ticks can sometimes be mistaken for a mole, melanoma or other nevi. Dermoscopy can play vital role in detecting the attached tick, identifying its genus and species. It also helps to confirm the complete separation of tick or whether residual parts of tick hypostome are left behind after removal from human skin.